Association of Lower Genital Tract Inflammation With Objective Evidence of Endometritis - Jeffrey F. Peipert; Roberta B. Ness; David E. Soper; Debra Bass (Hindawi Limited, 2000)
The purpose of this report is to evaluate the association between lower genital tract inflammation and objectively diagnosed endometritis. We analyzed the first 157 patients enrolled in the PEACH study, a multicenter randomized clinical trial designed to compare the effectiveness of outpatient and inpatient therapy for PID. Women less than 38 years of age, who presented with a history of pelvic discomfort for 30 days or less and who were found to have pelvic organ tenderness (uterine or adnexal tenderness) on bimanual examination, were initially invited to participate. After recruitment of the first 58 patients (group 1) we added the presence of leukorrhea, mucopurulent cervicitis, or untreated positive test for N. gonorrhoeae or C. trachomatis to the inclusion criteria (group 2, N = 99). We compared rates of endometritis in the two groups and calculated the sensitivity, specificity, and predicted values of the presence of white blood cells in the vaginal wet preparation. The rate of upper genital tract infection in group 1 was 46.5% (27/58) compared to 49.5% (49/99) in group 2. Microbiologic evidence of either N. gonorrhoeae or C. trachomatis increased from 22.4% in group 1 to 38.3% in group 2. The presence of Vaginal white blood cells or mueopus has a high sensitivity (88.9%), but a low specificity (19.4%) for the diagnosis of upper genital-tract infection. Assessment of the lower genital tract for evidence of infection or inflammation is a valuable component of the diagnostic evaluation of pelvic inflammatory disease. The presence of either mucopus or vaginal white blood cells is a highly sensitive test for endometritis in patients with pelvic pain and tenderness. Infect. Dis. Obstet. Gynecol. 8:83-87, 2000.